18 F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography-Positive Lymph Node Endometriosis Masquerading as Lymph Node Metastasis of a Malignant Tumor. (10th August 2014) - Akiyama, Makoto; Suganuma, Izumi; Mori, Taisuke; Kusuki, Izumi; Kuroboshi, Haruo; Ito, Fumitake; Matsushima, Hiroshi; Sawada, Morio; Kitawaki, Jo
Abstract : Endometriosis is defined as the presence of endometrium-like tissues at extrauterine sites, most commonly in the abdominal cavity. Lymph node endometriosis is a rare but clinically important type of endometriosis that can mimic lymph node metastasis of a malignant tumor. 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) is a useful tool for diagnosing malignant tumors, although it occasionally shows false positive results in tissues with high metabolic activity caused by severe inflammation. In the present report, we describe a case of lymph node endometriosis that mimicked lymph node metastasis of a malignant tumor and showed a positive result on 18 F-FDG PET/CT. The findings of the present case suggest that lymph node endometriosis could present as swollen lymph nodes with 18 F-FDG PET/CT-positive results and provide important information for determining an appropriate treatment strategy.